Social Media Marketing Strategies Based on CRM Value Chain Model - Maede Nemati; Gerhard Weber (International Journal of Innovation in Marketing Elements)
Despite the fact that social media marketing has a long history, new marketing methods and the rise of digital marketing have transformed it. Social media marketing's aims, tactics, and approaches are all centered on the consumer, thus there's a strong link between this sort of marketing and existing customer relationship management (CRM). This essay aims to investigate this connection and clarify the findings in order to better social media marketing efforts. This study's methodology is based on the value chain model, which is one of the CRM models. This approach considers customers, network, and management to deliver effective communication for value creation based on work processes, data, and information, as well as organizational leadership. We extract the effective and reciprocal variables between CRM and social media marketing in this study. The findings suggest that, using the proposed model, new social media marketing strategies may be proposed that generate incentives to share organizational resources in order to attract new customers through the media, pay attention to customer branding, and develop specific capabilities. This type of information technology is used.